Singapore's Intentions in Signing the Decarbonization Cooperation Framework with Indonesia through Carbon Capture Storage - Annindya, Jasmine Marshanda Rully; Sofie, Jasmine Nabila; Al Putra, Ferdian Ahya (Department of International Relations Universitas Pertamina, 2024)
This paper examines Singapore's intentions in signing the Carbon Capture Storage (CCS) cooperation framework with Indonesia. A qualitative descriptive methodology combining primary and secondary data sources was applied to get informative results. The concept used in this research is the international regime, alongside the cooperation theory by Holsti. The analysis shows that Singapore has the decarbonization roadmap to reduce the greenhouse gas emissions they have produced through cooperating with another country in CCS. The results reveal that the commitment reflects Singapore's responsibility in accordance with the Paris Agreement as an international regime. Singapore's rationalization in cooperating with Indonesia is based on the geography of Indonesia’s reservoir that is close to Singapore’s central industrial and power plant, Jurong Island. Singapore could cut costs by transferring carbon through pipelines to Indonesian sediment. This research underscores the significant role of bilateral cooperation in shaping the future trajectory of climate change amidst increasing global pressures through the Paris Agreement.